(untitled) (Itinera, 2024)
As it is well known, rhetoric serves as a theoretical framework for the foundation of artistic practices in the works of Leon Battista Alberti. The structural significance of rhetoric also concerns the conceptualization of the relationship between time, space, and memory. In Alberti’s perspective, ruins and fragments from the past are material incarnations of rhetorical-mnemonic imagines agentes: their power to affect the mind depends on the ability of the observer to put them in the right places (loci). Against this background, Alberti partially overturns the classical model of the ars memoriae: the a priori architectural order of loci becomes the result of an activity of composition and combination, in which the imagines/ruins disrupt the flow of time and the continuum of space by displaying their specific nature as memory traces.